Some Directions for Mediumship Research - Kelly, Emily Williams (Journal of Scientific Exploration, 2010)
The study of mediums was part of a larger program of psychical research, begun in the late 19th century, intended to examine specifically whether human personality survives bodily death, and more generally whether the brain produces mind or consciousness, as most scientists since the late 19th century have assumed. Although a vast amount of high-quality research resulted from that effort, the study of mediumship was almost completely abandoned during the latter half of the 20th century, primarily because of the impasse reached over whether the phenomena are best-interpreted as attributable to deceased agents or to living agents. In this paper the author examines some types of mediumship research that have been considered particularly important for the survival question: cross-correspondences, drop-in communicators, and proxy cases. She argues that a revival of research on mediumship, particularly with proxy sittings, could contribute importantly to present-day psychical research and, perhaps ultimately, move us beyond the current impasse. Keywords: mediumship–survival–proxy research–cross-correspondences–drop-in communicators